From state-bound subjects to global subjects: notes toward an Althusserian theory of globalized subjectivity. Issue 4 (18th May 2020) - Pfeifer, Geoff
ABSTRACT: This article puts Louis Althusser's conception of subjective production via ideological interpellation in dialogue with contemporary Global theories – especially those of Saskia Sassen and Manfred Steger. It does this to offer a more robust framework for understanding subjective production that captures subjective transformations in the age of globalization. The article looks at how Sassen's work captures transformations of social and institutional structures in globalization and then looks at Steger's account of subjective transformations. It then turns to the ways in which Althusser's understanding of the intertwining of subjectivity with institutions and social practices can help bridge the gap between Sassen and Steger and can also help us understand the rise of what I call 'global subjects' and a 'global subjectivity' that can be in conflict with more traditional 'state-bound' subjects. I use the example of globalized regimes of care work in order to help make sense of these distinctions.